(untitled) (diségno, 2021)
Some people who have made history with geographical discoveries and contributed to the evolution of knowledge about our planet have translated the emotion of their discoveries into drawings. In this text, we examine three examples of graphical narratives testifying to great geographical and scientific discoveries. The first is the axonometric drawing of Timbuktu by René Caillié, which presented for the first time an image of this place made mythical by the difficulty of reaching it. The second consists of the profiles and painted cards of landscapes observed by a 22-year-old Charles Darwin as seen from the sea while sailing on the Beagle between South America and Oceania, unknown worlds at the time. The third example is the geographical exploration of David Livingstone in Africa, which culminated in a very interesting drawing of Victoria Falls, which was unknown before then. This image also informs us about the explorers’ specific interest in reportage drawing, given the inclusion in Livingstone’s group of the graphic artist and painter Thomas Baines, who would follow the exploration to depict the most unexpected views that the group observed. What emerges is the role of drawing as an original testimony for distant observers, but also as a story of strong emotion and fascination with discovery at the limit of distorted vision, where emotion prevails over scientific data, sentiment over objective narration.